Trapped in the nursery: poor growth and condition in juvenile alewives (Alosa pseudoharengus) stemming from drought-imposed loss of connectivity to marine habitat - Michael N. Burgess; Ryan Adams; James Knighton; Eric T. Schultz (Frontiers in Marine Science, 2026)
Introduction Nursery habitats sustain populations only when individuals are able to move to habitats used by later life stages. For anadromous fishes such as Alewife ( Alosa pseudoharengus ), anthropogenic barriers and drought can disrupt this connectivity, entrapping juveniles and potentially depressing year-class success. We hypothesized that drought, by preventing juveniles prepared to emigrate from the nursery, maintains them at relatively high densities and keeps forage at relatively low levels, thus depressing growth rates and body condition. Methods Juvenile Alewife were sampled at the outlet of Bride Lake in East Lyme, Connecticut during a non-drought year and a prolonged drought year. We measured total length and dry mass, determined daily age from otoliths, quantified condition using the residual mass index, and estimated daily growth over the lifetime as well as in stanzas from 0 to 30 days, 0 to 100 days, and 70 to 100 days post hatch. Our sampling design enabled us to distinguish between year differences between early migrants and late migrants, who would be most affected by entrapment in the drought year. Results The hypothesis was supported by data. Seasonal increase in size of emigrating fish was 50% lower in the year of drought than the previous year. Late emigrants that had been entrapped had reduced condition, grew less over their lifetime, and had lower condition than their counterparts the previous year. While growth over the first 30 days post-hatch, prior to the onset of drought, did not differ between years, growth from 70 to 100 days post-hatch, coincident with a period of drought in the second year, was less than that in the previous year. Discussion Drought-induced entrapment curtailed growth and reduced size and condition of late-season juveniles, consistent with density-dependent competition, diminished forage, and declining autumn temperatures. Conservation of species of concern like the Alewife should prioritize maintaining juvenile connectivity. Future work should quantify entrapment-related mortality, extend drought forecasting to guide water management that minimizes the probability of entrapment, and integrate entrapment processes into population models to evaluate long-term consequences for Alewife recovery.